Behavioral Variant Frontotemporal Lobar Degeneration with Amyotrophic Lateral Sclerosis with a Chromosome 9p21 Hexanucleotide Repeat - Friedland, Robert; Shah, Jignesh; Farrer, Lindsay; Vardarajan, Badri; Rebolledo-Mendez, Jovan; Mok, Kin; Hardy, John (Frontiers in Neurology, 2012)
To determine the genetic basis of familial frontotemporal lobar degeneration (FTLD) with amyotrophic lateral sclerosis (ALS) we performed a clinical and genetic analysis of an affected family. A 51-year-old man with behavioral variant frontotemporal lobar degeneration with amyotrophic lateral sclerosis had a family history of the disease suggestive of autosomal dominant inheritance with incomplete penetrance. Genetic studies in this patient demonstrated the presence of an amplified hexanucleotide repeat (>30) polymorphism in the chromosome 9 open reading frame 72 (C9ORF72) gene which was previously identified as a cause of FTLD. Five others unaffecteds from the family were negative (all had less than 11 repeats). We did not find association of single nucleotide polymorphisms (SNPs) in C9ORF72 gene with Alzheimer’s disease (AD) risk using a large genome wide association study dataset. Bioinformatic analysis of C9ORF72 using the Gene Expression Omnibus database showed expression differences in patients with muscular dystrophy, neural tube defects and schizophrenia. We also report analysis of gene expression in brain regions using the Allen Human Brain Atlas. Defects in this recently reported gene are now believed to be the most common cause of inherited ALS and an important cause of inherited FTLD. Our work suggests that the gene may also be important in other neurological conditions.